2021
DOI: 10.1001/jama.2021.20714
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of High-Flow Oxygen Therapy vs Conventional Oxygen Therapy on Invasive Mechanical Ventilation and Clinical Recovery in Patients With Severe COVID-19

Abstract: IMPORTANCEThe effect of high-flow oxygen therapy vs conventional oxygen therapy has not been established in the setting of severe COVID-19.OBJECTIVE To determine the effect of high-flow oxygen therapy through a nasal cannula compared with conventional oxygen therapy on need for endotracheal intubation and clinical recovery in severe COVID-19. DESIGN, SETTING, AND PARTICIPANTSRandomized, open-label clinical trial conducted in emergency and intensive care units in 3 hospitals in Colombia. A total of 220 adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
159
0
5

Year Published

2022
2022
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(195 citation statements)
references
References 27 publications
5
159
0
5
Order By: Relevance
“…Our study also found that shortness of breath and elevated serum concentrations of lactate were independently associated with ICU admission. This is concordant with what is reported in the literature, as only severe COVID-19 patients are admitted to ICU [ 32 , 33 ]. These factors are essential because they are easily identifiable by physicians on hospital admission and might guide them to early detection of patients at risk of developing severe disease.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also found that shortness of breath and elevated serum concentrations of lactate were independently associated with ICU admission. This is concordant with what is reported in the literature, as only severe COVID-19 patients are admitted to ICU [ 32 , 33 ]. These factors are essential because they are easily identifiable by physicians on hospital admission and might guide them to early detection of patients at risk of developing severe disease.…”
Section: Discussionsupporting
confidence: 92%
“…Concerns however persist on their potential aggravating role in airborne Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2) transmission. High-Flow Nasal Cannula (HFNC) oxygen therapy appears clinically beneficial for patients with COVID-19 but was discouraged earlier in the pandemic because of its aerosol-generating potential [ 1 , 2 ]. Accumulating non-clinical data indicate that HFNC is not associated with more dispersion of aerosols and large droplets compared to conventional oxygen delivery systems [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A later meta-analysis found HFNC reduced intubation rates compared to NIPPV (OR 0.48, 95% CI 0.31–0.73), as well as ICU mortality (OR 0.36, 95% 0.20–0.63) [ 33 ]. A randomized controlled trial (RCT) of patients with PaO 2 /FiO 2 < 200 and COVID-19 found those receiving HFNC were less likely to be intubated (34.3% vs. 51%) and more likely to experience clinical recovery in 28 days (77.8% vs. 71%) compared to those receiving conventional oxygen [ 34 ].…”
Section: Discussionmentioning
confidence: 99%